An update on Kalecki–Minsky modelling - Engelbert Stockhammer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
Within post-Keynesian macroeconomics, the Kaleckian streams analysing demand regimes and the Minskyan streams analysing financial instability have proceeded relatively independently. To develop a comprehensive alternative to mainstream economics, post-Keynesians will have to integrate Kaleckian and Minskyan arguments with an analysis of the supply side. This paper gives a partial update on advances in Kalecki-Minsky modelling. First, theoretically, it discusses the notion of pseudo-Goodwin cycles. Second, it presents empirical findings on endogenous debt cycles. Third, it reviews evidence of the relative size of distributional and financial effects on demand. Fourth, it reports results on the drivers of household debt.
Keywords: E12; E32; E44; 330; post-Keynesian economics; Kalecki; Minsky; debt cycles; household debt